Strategi penterjemahan kata sendi nama Arab ke Bahasa Melayu : satu analisis deskriptif dan semantik dalam novel "Masrur dan Makrur" / Muhammad Luqman Ibnul Hakim B Mohd Saad - Muhammad Luqman Ibnul Hakim, Mohd Saad (2012)
This study is a descriptive and semantic analysis of the Arabic Prepositions من، إلى، عن، على، في، الباء، اللام ] ] translated into Malay language in the novel Masrur & Makrur. Its main aims are to identify the strategies and styles used to translate the prepositions and to analyze their meanings, semantic functions in verbal phrase (collocations and idioms) which were translated into Malay. Analysis of the results enabled the study to come up with a strategy of translating Arabic prepositions into the Malay language. This study applied the Dynamic, Semantic and Communicative Theories as well as the Relevance Theory to analyze the main data in terms of phrases, methods of translation and meanings in contexts of the target text. The results show that the Arabic and Malay (translation) prepositions consist of grammatical categories which cannot be translated into direct lexicals. Instead there is a need to look at sentence structure, syntax, grammatical rules, and semantics aspects as the more suitable contexts because these prepositions do not show their meanings unless they are used with other phrases. In conclusion, not all Arabic prepositions can be translated using the literal translation strategy except in certain circumstances, and omission of the meanings of Arabic prepositions are allowed as long as they do not affect the message of the texts. The translator should be concern with understanding the meanings and functions of the Arabic prepositions before beginning the translation process. This study has brought to light some points which a translator can use as guidance in translating Arabic prepositions into the Malay language.